Harvesting Success: Impact Measurement and Management as a Catalyst for Agribusiness Growth and Food Systems Transformation - Jaquet, Stephanie; Jalango, Dorcas; Giombini, Valentina; Wamicwe, Peter; Derenoncourt, Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The masterclass on Climate-Smart Agriculture and Agribusiness Impact was delivered at Africa Food System Forum in Dar Es Salaam covering a diverse range of topics aimed at equipping participants with the knowledge and tools necessary to navigate the challenges posed by climate change in the agricultural sector. Divided into three sections, the masterclass delved into Agribusiness Sustainability through Climate Smart Approaches, Harvesting Success by Crafting Business Impact Pathways, and Attracting Investment through Impact-Driven Approaches. Each section addressed critical questions, including the identification and prioritization of Climate-Smart Agriculture (CSA) investments, the crafting of impact pathways to measure societal impact, and strategies to attract investment through climate-sensitive approaches. The presenters provided valuable insights into the pillars of CSA, the importance of blending finance to reduce credit costs, and the need for climate-smart business models.